Curable resin composition, cured product thereof, printed circuit board comprising the same, and method for producing the cured product - OKAMOTO DAICHI; OKADA KAZUYA; MINEGISHI SHOJI; WEI XIAOZHU; YAMAMOTO SHUICHI (2016)
An alkaline development-type curable resin composition having an excellent strength against tearing, breaking, distortion and torsion, and excellent toughness, a cured product of the curable resin composition, a printed circuit board having the cured product, and a process for manufacturing the cured product are disclosed. A curable resin composition is obtained, which contains (A) a thermoplastic resin, (B) a thermosetting component, (C) an alkali-soluble component, and at least one of (D-1) a photopolymerization initiator and (D-2) a photo-base generator, the thermoplastic resin (A) having two or more glass transition points including two glass transition points Tgx and Tgy, which satisfy Tgx>30° C. and Tgy<0° C. and the thermosetting component (B) having a glass transition point Tgz, which satisfies Tgz Tgy+20° C. Moreover, a cured product of the curable resin composition, a printed circuit board having the cured product, and a process for manufacturing the cured product are obtained.